The influence of age and approaching death on the course of nondopaminergic symptoms in Parkinson's disease. (March 2016) - van Rooden, S.M.; Verbaan, D.; Stijnen, T.; Marinus, J.; van Hilten, J.J.
Abstract: Introduction: The influence of approaching death in addition to age and their interaction on the course of a broad spectrum of nondopaminergic features in Parkinson's disease (PD) has not been well studied. This study addresses this issue in a prospectively designed study. Methods: During five years, the severity of axial symptoms, cognitive impairment, psychotic symptoms, autonomic dysfunction, depressive symptoms, and daytime sleepiness was annually evaluated in PD patients. For each domain a linear mixed-effect model was used to examine changes during follow-up and relations with age and death. Results: Of 378 included patients, 43 died during follow-up. Higher age was associated with increased severity of all nondopaminergic features except depression, and with a higher rate of progression of axial symptoms and cognitive impairment. Patients who died during follow-up had a higher severity of all nondopaminergic features except autonomic dysfunction, and a higher rate of progression of axial symptoms, cognitive impairment, and psychotic symptoms, compared to patients who survived. Conclusion: This study shows that the severity of most nondopaminergic features and the progression rate of axial and psychotic symptoms and cognitive impairment increase before PD patients die, independent of the influence of age. An interaction between age and approaching death did not have a significant effect on the course of the symptoms. Improving our understanding of the fundamental biology underlying these factors and the interaction with factors intrinsic to the disease, may have profound implications for the treatment of PD. Highlights: The course of nondopaminergic PD symptoms in relation to age and death was studied. Patients who died during follow-up had more severe nondopaminergic symptoms. Progression of cognitive and axial symptoms accelerates in older patients. Progression of axial, cognitive, and psychotic symptoms accelerated before death.